Laboratory simulation of magnetospheric chorus wave generation. (18th October 2016) - Van Compernolle, B; An, X; Bortnik, J; Thorne, R M; Pribyl, P; Gekelman, W
Abstract: Whistler mode chorus emissions with a characteristic frequency chirp are important magnetospheric waves, responsible for the acceleration of outer radiation belt electrons to relativistic energies and also for the scattering loss of these electrons into the atmosphere. A laboratory experiment (Van Compernolle et al 2015 Phys. Rev. Lett .114 245002, An et al 2016 Geophys. Res. Lett .) in the large plasma device at UCLA was designed to closely mimic the scaled plasma parameters observed in the inner magnetosphere, and shed light on the excitation of discrete frequency whistler waves. It was observed that a rich variety of whistler wave emissions is excited by a gyrating electron beam. The properties of the whistler emissions depend strongly on plasma density, beam density and magnetic field profiles.